Cloning and expression of hGM-CSF in CHO-K1 cell line - Phung, Truong Hoang; Kim Bang, Ngo Thi; Hieu, Tran Van (Academia Journal of Biology, 2015)
GM-CSF (granulocyte-macrophage colony stimulating factor) is a cytokine with wide effects, not only on hematopoietic precursor cells, dendritic cells, but also on smooth muscle cells, epithelial cells and even neurons. Although, it does not play role in hGM-CSF biological functions, glycosylation enhances the protein in vivo stability. Therapeutic drugs containing recombinant hGM-CSF are mostly produced in Escherichia coli or Saccharomyces cerevisiae, which do not have post-translation modification mechanisms similar to those of humans. In this present study, the gene encoding for human (h)GM-CSF was transfected into the Chinese Ovary Cell (CHO)-K1 and expression of the protein was evaluated. Firstly, gene was inserted into the open reading frame after early promoter CMV at EcoRI and XhoI restriction sites. Recombinant vectors are screened by colony PCR, restriction enzyme digestion and sequencing. The recombinant vector was termed pcDNA-hGM and was transfected into CHO-K1 cells using cationic lipid method. Transformants was selected and maintained using antibiotic Geneticin. The results showed that the gene encoding for hGM-CSF was indeed cloned into pcDNA3.1+ vector at EcoRI and XhoI restriction sites. The conditioned medium collected from CHO‑K1/pcDNA-hGM stimulated the proliferation of TF-1, an hGM-CSF-dependent cell line. In summary, the recombinant vector pcDNA-hGM was cloned and the recombinant cell line CHO‑K1/pcDNA-hGM expressed active hGM-CSF. This is the first research on expression hGM-CSF in CHO-K1 cell line and providing evidence for further investigation on isolation and purification of hGM-CSF afterward.